2019
DOI: 10.33924/amt-2019-01-03
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Layer Thicknesses of a Model Produced by Fused Filament Extrusion

Abstract: Nowadays additive manufacturing continues to gain more and more space in industrial technology. In particular, FDM (fused deposition modelling) machines have become easily available to the public. Quality of parts is impacted by several factors. In this study we investigate layer thicknesses of a prototype manufactured from PLA, and we pay special attention to the thickness of sequentially deposited layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…60 He played an important role in setting up and equipping the Dental Clinic. 61 He was dismissed in 1946, and until his death he was the chief dentist of the Hungarian State Railways Hospital. 62 After his graduation in 1937, Dezső worked at the Clinic of Surgery, then between 1947 and 1982 at the Paediatric Clinic as the head of the Department of Otorhinolaryngology.…”
Section: Sourcebooksmentioning
confidence: 99%
“…60 He played an important role in setting up and equipping the Dental Clinic. 61 He was dismissed in 1946, and until his death he was the chief dentist of the Hungarian State Railways Hospital. 62 After his graduation in 1937, Dezső worked at the Clinic of Surgery, then between 1947 and 1982 at the Paediatric Clinic as the head of the Department of Otorhinolaryngology.…”
Section: Sourcebooksmentioning
confidence: 99%
“…Again, the main condition of success was cooperation between different troop types as the missile troops were always accompanying those designed for hand-to-hand combat. 31 Seventh century Assyrian infantry wore at least helmets but armours were very frequent. Most common were lamellar corselets but the discs covering crucial area of central rib cage were also frequent.…”
Section: Assyrian Military Capabilities In the 7th Centurymentioning
confidence: 99%
“…One concern about the efficacy of using AM to produce respirators is the intrinsic porosity in FFF- and PBF-produced parts, which can affect filtration efficiency, accuracy, and reliability of the printed respirators. In FFF processes, porosity can result from adjacent layers not fully fusing [ 12 , 13 ], gaps left from changing direction and stopping/starting melt extrusion, and/or gaps left from adjacent extruded paths failing to fuse together [ 14 , 15 ]. Such inherent, process-induced defects have been shown to cause up to 32% porosity in FFF parts, with 200–800 μm diameter pores [ 16 ], which could render them ineffective in protecting against 0.3 μm virus particles.…”
Section: Introductionmentioning
confidence: 99%
“…Another anticipated challenge in the use of AM to directly fabricate PPE through shared digital designs is the inherent variability between AM machines, materials, and build parameters [ 21 ], which can affect the mechanical properties of the printed materials and the accuracy of the printed geometries. In FFF, processing parameters such as layer thickness [ 12 ], layer orientation [ 22 ], raster width and spacing [ 23 ], and filament feed rate [ 14 ] influence porosity, part quality, and performance. Prior round robin studies have shown variation between parts/tolerances despite parts being made on similar FFF systems [ [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%